IMPLEMENTASI PERATURAN MENTERI ATR/BADAN PERTANAHAN NASIONAL NOMOR 6 TAHUN 2018 DI KABUPATEN SOLOK - Ikhsan, Mahgfiratul; ", Adianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Solok district is one of the areas with potential land that can be utilized and developed, such as the potential of agriculture and plantations, the potential of the fisheries sector, and tourism potential. Hence there are not infrequent conflicts and land issues, due to unclear land ownership in the community. Overcoming these problems the government elaborated a land registration policy through the ATR / National Land Agency Ministerial Regulation Number 6 of 2018 concerning Complete Systematic Land Registration. The purpose of this study was to determine the implementation of PTSL and see the inhibiting factors for the implementation of a complete systematic land registration program in Solok Regency. The theoretical concept used is the theory of implementation by Ripley and Franklin in (Tahir, 2015), namely: the level of bureaucratic compliance, smooth routines and no problems, and performance. This study uses qualitative methods with a phenomenological approach, with data collection techniques including: interviews and documentation. The results of this study found that the implementation of the ATR / National Land Agency Minister Regulation Number 6 of 2018 in Solok District was not maximal. Factors that hinder implementation are human resource factors and time constraints.Â Keywords: Policy, Implementation of Policy, Land Policy